Using semantic web technologies for analysis and validation of structural markup. (1st January 2011) - Di Iorio, Angelo; Peroni, Silvio; Vitali, Fabio
An increasing part of research in the Semantic Web has been directed at making data become the main concept of the web. Plenty of languages and specifications support this transition and work by inserting additional (semantic) markup into web documents. Yet, little attention is being paid to the possibility of expressing the actual structures of the documents in a form suitable for the semantic web. EARMARK is a model for explicitly expressing structural assertions of markup and documents, allowing a straightforward integration of the semantics of the markup and the semantics of the content. The well-formedness of a hierarchy, for instance, becomes an explicit assertion and similarly the analysis of the validity of markup structures become matter for further semantic analysis. This paper describes EARMARK and shows a framework for using OWL ontologies, that implement particular markup properties, to demonstrate the compliance of EARMARK documents with those properties.